Kombinasi Metode SWARA Dan MOORA Untuk Pendukung Keputusan Pemberian Insentif Karyawan - Eliani, Eliani; Murdani, Murdani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Giving Incentives for new employees at PT. Expravet Nasuba Medan An appreciation in the form of bonuses given to every employee with employee income outside the basic salary. The provision of these incentives is based on performance results. And also based on the criteria for providing employee incentives. The criteria include education, performance, length of service, seniority and achievement. Problems that often occur at PT. Expravet Nasuba Breeding Enterprise is the provision of employee incentives not fully, and the time given is not appropriate, and the administration department is not objective in the distribution of incentives. Based on these problems, the authors are committed to solving these problems with a decision support system made with a combination of SWARA and MOORA methods. Both of these methods are each able to create and solve problems with criteria and multi-criteria data in decision making. In providing employee incentives in the SWARA and MOORA methods, the swara method is used to obtain normal weights, and the weighting results will be calculated using the Moora method. While the moora method is used for ranking. The results of the combination of these methods with the highest value will be used as the final result in decision making. Of course, the benefits obtained from the method used is to facilitate the company's administration in providing employee incentives at PT. Expravet Nasuba Breeding Enterprise. The results obtained based on the combination of SWARA and MOORA methods that Kiki Putra Naisya is the best and highest alternative. The conclusion that can be drawn from the results of the study is that both SWARA and MOORA methods can be used to determine employee incentives at PT. Expravet Nasuba Breeding Enterprise